The framework for minimizing construction time and cost overruns in Padang and Pekanbaru, Indonesia - Harisaweni, Harisaweni (2007)
It has been said that Indonesian constructions often suffer serious cost and time overrun. Kaming et.al., (1997a) and Trigunarsyah (2004) have studied the causes of these problems. However, their studies focused only on the high rise buildings in Jakarta and Yogyakarta. Since Indonesia is a large country with more than 3000 islands, it pertinent to ask whether their findings are also applicable to low-rise constructions in other major cities in the country. It appeared that the low-rise constructions in Padang and Pekanbaru, the two major cities in Sumatera, are also facing the problems of time and cost overrun. The issues bring about some related questions â€“ what are the causes of these problems? Are they similar to the findings made by Kaming and Trigunarsyah? How do contractors and managers in Padang and Pekanbaru manage construction cost and time? Are they adhering to the good practice of project cost and time management? What is considered as the best time and cost management practice? What is good time and cost management framework or model like? Generally, the aim of this study is to answer all these questions. But more specifically, the main objectives are threefold; firstly, to identify the major causes of project time and cost overrun in low - rise projects in Padang and Pekanbaru; secondly, to develop and establish the theoretical framework of a good construction time and cost management practice, and thirdly, to compare the time and cost management as currently practiced by contractors and consultants in Padang and Pekanbaru against the â€œtheoreticalâ€? framework of the good time and cost management. The study focused on low-rise projects in Padang and Pekanbaru, Sumatera which are managed by contractors and consultants in class B and M respectively. The study looked at both from contractorsâ€™ and consultantsâ€™ perspectives. Data and information for the study are collected using a combination of documentary analysis and structured interview techniques. The data were systematically compiled and analysed using descriptive statistic techniques. The study shows that the major causes of project time and cost overrun in Padang and Pekanbaru ranges from lack of labour, lack of equipment to material delivery problems and frequent design changes. The study also highlighted that there are several approaches to efficient and effective project time and cost management. They can be summarized in the form of a framework or model that form the basis for the study. It is found that, generally contractors and consultants in Padang and Pekanbaru have adhered to the good time and cost management framework. However, the main area of concern is their lack of emphasis on the control aspects of the management. They are found to be lacking in monitoring the difference between planned and actual time and cost performance and identifying or establishing the deviation or problems associated with it. The study also pointed out that contractors and consultants in Padang and Pekanbaru need a clear and systematic project time and cost management framework that they can use as guidelines or reference for more efficient management.